EFFECT OF MOTIVATION AND INTERPERSONAL INTELLIGENCE ON THE QUALITY PERFORMANCE OF SANTRI ORGANIZATION MANAGERS - Sumiharsono, Rudy; Aisyah, Siti; Utomo, Bendot Tri; Arifin, Arifin; Ramadhan, Syahrul (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
This study aimed to examine the effect of motivation and interpersonal intelligence on the quality of performance of Santri organization managers. A total of 150 managers from various Santri organizations participated in the study. Data was collected using a questionnaire and analyzed using structural equation modeling. The results showed that motivation had a significant direct and indirect effect on the quality of performance of the managers through interpersonal intelligence. The direct effect of motivation on the quality of performance had an estimate of 0.41 and a p-value of 0.001, while the indirect effect had an estimate of 0.24 and a p-value of 0.001. The total effect of motivation on the quality of performance had an estimate of 0.66 and a p-value of 0.001. These results suggest that motivation and interpersonal intelligence play a significant role in improving the quality of performance of Santri organization managers. The findings of this study can provide useful information for organizations to improve the performance of their managers and increase their productivity.